Analysis of Legal Protection of Intellectual Property Rights from a Criminal Law Perspective - Rosita, Dian; Novitasari, Arina; Azizah, Naili; Cahyaningrum, Nila Maulida; Zuniarti, Zuniarti (JURNAL USM LAW REVIEW, 2025)
This research intention is to find out how the legal protection of Intellectual Property Rights (IPR) on TikTok video content is from a penal law perspective and to find out the penalties given to increase the effectiveness of law enforcement. The background of this research is based on the large number of uses of most of the songs on the Tiktok application without permission from the copyright holder who should have economic rights to their creations. This action can be categorized as a criminal act of piracy. A crime is an unlawful act that is detrimental to society and the perpetrators can be subject to criminal penalties. The development of communication technology has given birth to a new media called social media, and TikTok is one of the popular social media among the public. The problem is that most of the songs used in the Tiktok application are used without permission from the copyright holder who should have economic rights to their creation. The research method used in this study is the normative legal method with a statutory approach. The specifications of this study are descriptive analytical. The results of the study show that the criminal approach in the protection of Intellectual Property Rights is very important to ensure that the intellectual property rights of the results of creation are respected in society, the imposition of criminal sanctions in cases of violations, such as the use of songs without permission is important to provide a deterrent effect on the perpetrators while protecting the interests of the rights owners and creating legal certainty. The novelty of this research lies in the multidisciplinary approach that connects aspects of penal law with social and economic problems in the protection of Intellectual Property Rights.